The Role of Epidemiology, Nursing, Pharmacy, and Emergency Medicine in Managing Infectious Disease Outbreaks: An Integrated Approach - Al-Dalbahi, Ibrahim Ayed; Mufres, Bandar Mohammed; Mufres, Khaled Mohammed; Al-Hafi, Majid Sebaa; Al-Dalbahi, Mansour Nasser; Al-Azmi, Salem Marshoud; Ammar, Oqab Mutayliq; Jazzy, Salman Mutlaq (Journal of Ecohumanism, 2024)
Infectious disease outbreak is a recurring issue for global health with high disease, fatality, and burden for healthcare systems. Successful outbreak management is a multidisciplinary intervention with coordination between epidemiology, nursing, pharmacy, and emergency medicine with one another. All specialties have a complementary role in controlling an outbreak—evidence-guided interventions and epidemiologic surveillance through epidemiology, infection prevention and control through nursing, optimized stewardship of antimicrobial through pharmacy, and triage and early care through emergency medicine. All specialties together make a significant contribution in improving outbreak management, minimizing complications in a patient, and controlling infection dissemination. In this review, collaboration, contribution of specialties, and best practice in infectious disease outbreak management is focused.